Utilization of Instagram in Increasing Marketing Productivity of Bitata Food MSMEs - Syam, Hamdani M.; Sartika, Maini; Ghaitsa Al-Zahira Zulvita (UPT Publikasi Ilmiah UNISBA, 2025)
This study analyzed the proper digital marketing communication via Instagram in increasing marketing productivity, the aim to explain the marketing communication strategy on Instagram using the Yin case study method on Bitata Food MSMEs for 90 days (September-November 2023 period) by applying The Circular Model of Some concept as a guide through in-depth interviews with the owner and content creator of Bitata Food, then triangulated by marketing communication academic experts. The results highlight the anomalies in the concepts of marketing science, marketing algorithms on Instagram, and Bitata Food's marketing activities. Marketing productivity did not increase because the engagement rate was 1.53%, primarily due to suboptimal public involvement in the posted content, despite the correct strategy and eye-catching content. Given the dynamics of digital transformation, which are characterized by uncertainty, digital acceleration is necessary to survive and thrive in the competitive landscape. The output presents a new method for measuring marketing productivity on Instagram, in addition to the IMC strategy, and provides recommendations for evaluation to help MSMEs create marketing messages with emotional appeal. The most important thing is that the product is getting closer to the public.